The meaning and value of digital technology adoption for older adults with sight loss: A mixed methods study. - Fisher, Katherine; Easton, Katherine (Technology & Disability, 2019)
BACKGROUND: Sight loss adversely affects older adults' (> 65 years) ability to complete daily activities. Digital technology can support functional performance but literature focusing on its use by older people with sight loss is limited. OBJECTIVE: To explore the meaning of digital technology, including factors influencing its adoption, from the perspectives of older adults with sight loss. METHOD: In-depth data was generated via a focus group (n = 4) and analysed using thematic analysis. In addition, a questionnaire survey (n = 30) increased breadth of knowledge regarding digital device adoption. RESULTS: Following thematic analysis, digital technology was equated with complexity. Portable, easy-to-use technology and devices enabling meaningful outcomes were favoured. Barriers to adoption included: high cost, lack of accessible information, unreliability and constantly changing products. Conversely, resource exchange and an interest in technology facilitated acceptance. Physical properties, user interface, accessibility and practical experience concurrently hindered and supported device use. Survey results indicate that most non-digital adopters were > 80 years old, and commonly cited reasons were 'lack of interest' and 'too difficult to use'. CONCLUSION: Older adults with sight loss may be at particular risk of deeming digital technology to be inaccessible. Family and/or peer influence and experimenting with a device could challenge negative preconceptions.